7 - Les partis politiques et la démocratie au Mali: by Souleymane T. Koné - Souleymane T. Koné (Africa Development, 1998)
After decades of single party politics, Mali has shifted to integral multi-partyism with die formulation of 58 political parties and groupings. Such a situation has led to the erosion of the political landscape and to poor political representation, which is reflected by the proliferation of parties and low voter turnouts in elections. According to the author, society does not exist outside of die state, and a construction of the civil society has to be defined as such for the consolidation of democracy. Adding to the plethora of political patties, regrettably, are the extreme instability of political groups and the dispersal of energies, as well as internal divisions. Reinforcing political parties is an imperative necessity. Indeed, there is a need for a highly representative party system in which the formations maintain close links with different social groups. For the author, it is crucial to break free from die political pattern of the independence movements, that is to say, to introduce a democratic dimension in order to strengthen the national and social aspects creating them.